Consolidation of high water content soils in an estuarine environment - Bras, Gilbert Le; Alexis, Alain (Journal of Nepal Geological Society, 2000)
The constant silting up of ports and estuaries makes it necessary to carry out dredging operations to ensure free access to port infrastructure. The dredged materials are disposed of at sea, with the creation of a maritime deposit, or stored on land in decantation pools. In each case, this leads to the creation of high water content soil. This paper presents a geotechnical laboratory approach to the formation of high water content soils on an experimental sedimentation/consolidation test bench. The original feature of this test bench is that it is possible to carry out highly accurate pressure and density measurements in a time very close to the beginning of the test. These measurements are used to analyse the changes in the total stress, the pore pressure, and the effective stress. On a diagram showing the void ratio/effective stress, we have highlighted the changes in the intermediate phases of the formation of a natural soil which consolidates under its own weight.